Centrosomal ALIX regulates mitotic spindle orientation by modulating astral microtubule dynamics. (1st June 2018) - Malerød, Lene; Le Borgne, Roland; Lie‐Jensen, Anette; Eikenes, Åsmund Husabø; Brech, Andreas; Liestøl, Knut; Stenmark, Harald; Haglund, Kaisa
Abstract: The orientation of the mitotic spindle (MS) is tightly regulated, but the molecular mechanisms are incompletely understood. Here we report a novel role for the multifunctional adaptor protein ALG‐2‐interacting protein X (ALIX) in regulating MS orientation in addition to its well‐established role in cytokinesis. We show that ALIX is recruited to the pericentriolar material (PCM) of the centrosomes and promotes correct orientation of the MS in asymmetrically dividing Drosophila stem cells and epithelial cells, and symmetrically dividing Drosophila and human epithelial cells. ALIX‐deprived cells display defective formation of astral microtubules (MTs), which results in abnormal MS orientation. Specifically, ALIX is recruited to the PCM via Drosophila Spindle defective 2 (DSpd‐2)/Cep192, where ALIX promotes accumulation of γ‐tubulin and thus facilitates efficient nucleation of astral MTs. In addition, ALIX promotes MT stability by recruiting microtubule‐associated protein 1S (MAP1S), which stabilizes newly formed MTs. Altogether, our results demonstrate a novel evolutionarily conserved role of ALIX in providing robustness to the orientation of the MS by promoting astral MT formation during asymmetric and symmetric cell division. Synopsis: The multifunctional adaptor protein ALIX is recruited to centrosomes, where it plays a previously unrecognized, evolutionarily conserved role in regulating mitotic spindle orientation, by promoting the formation of astral microtubules during both asymmetric and symmetric cell division. DSpd‐2/Cep192 promotes ALIX recruitment to the pericentriolar material of centrosomes in both fly and human cells. ALIX facilitates nucleation of astral microtubules by recruiting γ‐tubulin to centrosomes. ALIX promotes astral microtubule stabilization via recruitment of MAP1S to centrosomes. Reduced astral microtubule formation in ALIX‐depleted cells results in mitotic spindle misorientation. ALIX promotes correct metaphase spindle orientation in Drosophila stem cells and epithelial cells, as well as in human epithelial cells. Abstract : A novel, conserved role for the multifunctional adaptor protein ALIX in facilitating centrosome recruitment of γ‐tubulin and MAP1S ensures correct spindle orientation during both asymmetric and symmetric cell division.